2019
DOI: 10.3389/fneur.2019.00917
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Cardiomyopathy—Acute Cardiac Dysfunction Associated With Neurological and Psychiatric Disorders

Abstract: Takotsubo cardiomyopathy (TTC) is an acute and reversible cardiac wall motion abnormality of the left myocardium. Although many studies focused on etiology, diagnostic and treatment of TTC, precise clinical guidelines on TTC are not available. Research revealed emotional and physical triggering factors of TTC and emphasized the association of TTC with psychiatric and particularly acute neurological disorders. Similar clinical presentation of acute coronary syndrome (ACS) and TTC patients, makes an anamnestic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
1
21
1
Order By: Relevance
“…The hypothalamic-pituitary-adrenal axis (HPA-axis) is a major neuroendocrine system which regulates the release of cortisol from the adrenal gland, shifting the metabolism to higher stress levels. Higher serum cortisol levels and increased sympathetic activity may cause myocardial damage ( 5 ). Consequently, acute psychological or physical stress mediated via the sympathetic-adrenal- medulla axis with catecholamine release in the adrenal medulla and the HPA axis with consecutive cortisol release from the adrenal cortex may act as a trigger for TC ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothalamic-pituitary-adrenal axis (HPA-axis) is a major neuroendocrine system which regulates the release of cortisol from the adrenal gland, shifting the metabolism to higher stress levels. Higher serum cortisol levels and increased sympathetic activity may cause myocardial damage ( 5 ). Consequently, acute psychological or physical stress mediated via the sympathetic-adrenal- medulla axis with catecholamine release in the adrenal medulla and the HPA axis with consecutive cortisol release from the adrenal cortex may act as a trigger for TC ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher serum cortisol levels and increased sympathetic activity may cause myocardial damage ( 5 ). Consequently, acute psychological or physical stress mediated via the sympathetic-adrenal- medulla axis with catecholamine release in the adrenal medulla and the HPA axis with consecutive cortisol release from the adrenal cortex may act as a trigger for TC ( 5 ). Additionally, regional differences in myocardial expression of β2-adrenergic receptor density have been shown, which mediate the cellular effects of the increased catecholamine blood concentrations and explain the regional left ventricular myocardial stunning ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The typical patient with primary TTS is a post-menopausal woman who has experienced severe, unexpected emotional or physical stress [4,28]. Some authors have recently described that in patients with pre-admission anxiety disorders, TTS was predominantly triggered by exclusively emotional stress.…”
Section: Tts Triggers In Patients With and Without Pre-admission Anximentioning
confidence: 99%
“…Although the pathophysiology of TTS is not fully understood, much evidence has been documented. At the very beginning, spasms of coronary arteries were identified as TTS's underlying mechanism, although this hypothesis was later refuted [28]. However, it is well known that brain neurons that mediate vasoconstriction innervate coronary microcirculation, supports the concept that regional myocardial stunning among patients with TTS may be of neurogenic origin [22].…”
Section: Takotsubo and Anxiety Disorders: Pathophysiologic Connectionsmentioning
confidence: 99%
“…With interest we read the review article by Buchmann et al about Takotsubo cardiomyopathy (TTC), an acute reversible heart failure syndrome, triggered by neurological or psychiatric disorders (1). The authors concluded that the international expert consensus document on TTC, published by Ghadri et al (2), “should be used in the daily clinical routine to provide excellent patient care” (1). We have the following comments and concerns.…”
mentioning
confidence: 99%